Comparison of Foundation Strength Modelling of Jacket Platforms in API RP2A codes and ISO 19902 - Idrus, Arazi (2010)
Comparison of three offshore jacket platform codes i.e. API RP2A-WSD (21st edition, 2008) API RP2A-LRFD (1st edition, 2003) and ISO 19902 1st edition, 2007) is made on the foundation strength modelling. A detailed comparison of the provisions of the codes is useful to understand the provisions as well in the process of calibration of the load and resistance factors used in design. Guidance provided in the codes does not specifically apply to problem soils of carbonate material, volcanic sands or highly sensitive clays. All code contains guidance against static and monotonic loading. In this paper, the related equations are identified and compared and the similarities and differences are shown.